'Dream', 'Spellbound' and 'Skin'. Issue 2 (1st June 2021) - Siklosi, Kate
With these pieces, I'm exploring the rich history of wimmin's handicraft as a feminist poetic praxis. In today's saturated, technomediatic world, domesticity and handcraft often get left out of discussions of 'media ecologies'. What happens when we incorporate the feminist practices of care, fragility, uniqueness, domesticity and craft into an increasingly digitized and mass-produced means of publishing and sharing literary work? Using found objects, Letraset and thread, these 'offline' poetic works explore an unmediated intimacy with poetic materials; in the tactility of hand-to-object care and contact, an oft overlooked ethics of intimacy and vulnerable surfaces. With these pieces I am also thinking alongside the work of feminist theorist Sara Ahmed who thinks of feminism as 'a fragile archive, a body assembled from shattering, from splattering, an archive whose fragility gives us responsibility: to take care'. Against the masculinist impulse for permanence and enduring legacy in poetics, these pieces make space for radical openness: working with transient and precarious materials and media not only quells the ego, but allows for a greater responsiveness to and engagement with the world and the conditions that shape it.